Optimising plant growth, biomass partitioning, and nitrogen use efficiency in taro (Colocasia esculenta (L.) Schott) - Steel, Laura; Antille, Diogenes L.; Gleadow, Roslyn M. (Frontiers in Plant Science, 2026)
IntroductionTaro (Colocasia esculenta) is the fourth most important root crop globally, yet it remains understudied. Productivity is frequently constrained by nutrient-depleted soils. This study investigates how varying nitrogen (N) levels affect taro growth, particularly biomass accumulation, sucker production, and the formation of calcium oxalate raphides, which can be harmful when ingested. We hypothesized that: (1) Growth and photosynthetic rate are highest in plants receiving the highest concentration of nitrogen; (2) Optimal corm development occurs when N is neither deficient nor excessive; (3) Sucker production increases when corm N needs are met; (4) Tissue calcium concentration (a proxy for calcium oxalate) rises when growth is limited by N.MethodsTaro plants were grown using nutrient solutions with N concentrations ranging from 2.5 to 20 mM N. Plants were harvested at different growth stages up to 10 months to capture corm formation, filling, maturity and post-maturity stages. Biomass and nutrient concentrations were measured and nitrogen use efficiency indices were calculated.ResultsThe highest overall biomass was at 15 mM N, but corm biomass was highest in plants grown at the 5 and 10 mM N treatments. Sucker number and biomass increased with N concentration. Calcium concentration showed a strong positive correlation with N in corms but a weak negative correlation in leaves.Discussion/conclusionHypotheses 2 and 3 were supported; Hypothesis 1 was not. The optimal N level for maximizing corm biomass without compromising nutritional quality is around 10 mM N. These findings will inform biophysical models for taro to help its development as a food and nutrition security crop.